Mechanobiological Mimicry of Helper T Lymphocytes to Evaluate Cell–Biomaterials Crosstalk. Issue 23 (23rd April 2018) - Hasani‐Sadrabadi, Mohammad Mahdi; Majedi, Fatemeh S.; Bensinger, Steven J.; Wu, Benjamin M.; Bouchard, Louis‐S.; Weiss, Paul S.; Moshaverinia, Alireza
Abstract: The unique properties of immune cells have inspired many efforts in engineering advanced biomaterials capable of mimicking their behaviors. However, an inclusive model capable of mimicking immune cells in different situations remains lacking. Such models can provide invaluable data for understanding immune–biomaterial crosstalk. Inspired by CD4+ T cells, polymeric microparticles with physicochemical properties similar to naïve and active T cells are engineered. A lipid coating is applied to enhance their resemblance and provide a platform for conjugation of desired antibodies. A novel dual gelation approach is used to tune the elastic modulus and flexibility of particles, which also leads to elongated circulation times. Furthermore, the model is enriched with magnetic particles so that magnetotaxis resembles the chemotaxis of cells. Also, interleukin‐2, a proliferation booster, and interferon‐γ cytokines are loaded into the particles to manipulate the fates of killer T cells and mesenchymal stem cells, respectively. The penetration of these particles into 3D environments is studied to provide in vitro models of immune‐biomaterials crosstalk. This biomimicry model enables optimization of design parameters required for engineering more efficient drug carriers and serves as a potent replica for understanding the mechanical behavior of immune cells. Abstract : Super‐soft functional microparticles, capable of penetrating 3D porous microenvironments like natural T cells are developed. These particles have prolonged blood circulation and can release various cytokines on demand. These microscale particles offer simple and accurate ways to perform proof‐of‐concept studies in the context of immune–biomaterial or immune–stem‐cell interaction in dynamic or static conditions.